2023
DOI: 10.1111/mcn.13588
|View full text |Cite
|
Sign up to set email alerts
|

Overpromoted and underregulated: National binding legal measures related to commercially produced complementary foods in seven Southeast Asian countries are not fully aligned with available guidance

Jessica Blankenship,
Tuan Nguyen,
Jessica M. White
et al.

Abstract: The market for commercially produced complementary foods (CPCF) is rapidly expanding in Southeast Asia; however, the existence and content of mandatory national policies, standards and legislation (binding legal measures) for CPCF in the region is unclear. To assess the status of national binding legal measures for CPCF in Southeast Asia, a legal and policy desk review was conducted in seven countries (Cambodia, Laos People's Democratic Republic, Indonesia, Malaysia, Philippines, Thailand and Viet Nam). The al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In this issue, Blankenship et al ( 2023 ) reviewed mandatory national policies, standards and legislation (binding legal measures) relevant to CPCF in the seven COMMIT countries and compared their alignment to the six relevant Codex Standards and Guidelines (Codex Alimentarius, 1981 , 2004 , 2006 , 2011 , 2013 , 2018 ), the WHO Guidance (WHO, 2017 ) and the nutrient composition and labelling requirements in an adapted version of the WHO Europe NPM for CPCF. In the first analysis of this kind globally, the authors found that no country was fully aligned with the available global guidance.…”
Section: Summary Of Evidence Presented In This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, Blankenship et al ( 2023 ) reviewed mandatory national policies, standards and legislation (binding legal measures) relevant to CPCF in the seven COMMIT countries and compared their alignment to the six relevant Codex Standards and Guidelines (Codex Alimentarius, 1981 , 2004 , 2006 , 2011 , 2013 , 2018 ), the WHO Guidance (WHO, 2017 ) and the nutrient composition and labelling requirements in an adapted version of the WHO Europe NPM for CPCF. In the first analysis of this kind globally, the authors found that no country was fully aligned with the available global guidance.…”
Section: Summary Of Evidence Presented In This Special Issuementioning
confidence: 99%
“…Only one country was in full alignment with the WHO Guidance and no country was fully aligned with the adapted version of the WHO Europe NPM for CPCF. The findings from Blankenship et al ( 2023 ) indicate that existing legal measures in the COMMIT countries in Southeast Asia are insufficient to ensure CPCF are nutritionally adequate and appropriately labelled.…”
Section: Summary Of Evidence Presented In This Special Issuementioning
confidence: 99%